STRATEGI PENGELOLAAN ZAKAT PRODUKTIF DALAM PENGENTASAN KEMISKINAN (STUDI KASUS LEMBAGA ZAKAT MUHAMMADIYAH KOTA MEDAN) - AL Bara; Riyan Pradesyah; Nurman Ginting (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2019)
The purpose of this study was to look at the system of providing productive zakat funds in the Muhammadiyah zakat institution in Medan City. The current management of zakat still causes controversy. Where, the distribution of zakat funds is still less effective. The zakat management institution shows less transparent and accountable performance. The principle of justice is something that must be enforced. Where, the intended justice is being able to manage and distribute the zakat funds appropriately and quickly. The implementation of zakat in alleviating poverty and improving the economy should be immediately relocated through improving the performance of the zakat institution itself. Because the role of zakat on the lives of mustahik is very strategic if managed wisely. The development of productive zakat, which should be an alternative in alleviating poverty, is now a financing provided to the community. In fact, productive zakat is the provision of funds to mustahik or the poor, in the development of the economy, not the provision of funding that must be returned to the zakat institution. So for that, here the researcher wants to see the concept of giving productive zakat to the Muhammadiyah zakat institution in Medan. This research will be carried out for 3 months and will carry out observations and conduct direct interviews with the Muhammadiyah Zakat Institution in Medan City.To achieve the results of this study, this study uses a qualitative descriptive research method where researchers are actively involved in meeting, observing, and interviewing participants to uncover productive zakat management strategies in alleviating poverty, with the case study of the Medan City Muhammadiyah Zakat Institute.